2020
DOI: 10.1021/acsaem.0c00702
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability of Inverted and Flexible Perovskite Solar Cells with Carbon Electrode

Abstract: We demonstrate highly efficient, stable, and flexible perovskite solar cells of large areas, utilizing a carbon back-contact electrode in a p–i–n cell configuration. We enabled good electronic contact at the interface with carbon by inserting an ultrathin buffer layer before the carbon coating. Solar cells of such structure reach a power conversion efficiency of 15.18% on PET foil (device area of 1 cm2). We performed impedance spectroscopy and transient decay measurements to understand the electron transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 33 publications
(52 reference statements)
2
104
1
Order By: Relevance
“…50%) for 1680 h. Recently, Babu et al demonstrated carbon-based flexible perovskite solar cells in the p-i-n configuration on PET foil. 163 The devices with an active area of 1 cm 2 delivered an efficiency of 15.18% and excellent operational (MPPT) and thermal (85 1C) stability over 1000 h of ageing. This journal is © The Royal Society of Chemistry 2020…”
Section: Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…50%) for 1680 h. Recently, Babu et al demonstrated carbon-based flexible perovskite solar cells in the p-i-n configuration on PET foil. 163 The devices with an active area of 1 cm 2 delivered an efficiency of 15.18% and excellent operational (MPPT) and thermal (85 1C) stability over 1000 h of ageing. This journal is © The Royal Society of Chemistry 2020…”
Section: Reviewmentioning
confidence: 96%
“…Recently, Babu et al demonstrated a Cr buffer layer inserted between the electron transport layer and carbon electrode as a way to obtain Ohmic contact at that interface and efficient This journal is © The Royal Society of Chemistry 2020 charge collection in p-i-n devices. 163 They reported 15.18% PCE for a flexible perovskite solar cell (Fig. 31) with a large active area of 1 cm 2 .…”
Section: View Article Onlinementioning
confidence: 97%
“…As a matter of fact, most of the efficient and highly expensive organic hole-transporting materials (HTMs) (e.g., Spiro-OMeTAD) are operationally unstable and are inclined to mediate migration of halide and metal ions of noble metal counter-electrodes which are conventionally used (e.g., Au, Ag, and Al) [7][8][9]. Among the non-conventional proposed architectures, hole-transporting-layer-free Carbon-based PSCs (HTL-free C-PSCs) are promising candidates due to their superior long-term stability and low cost [10][11][12][13] that compensate the lack of carrier selectivity with respect to the application of a hole transporting material. Carbon-based top contacts for HTL-free PSCs are made using carbon pastes (mix of graphite flakes, carbon black, curing resin and solvent) deposited directly on the perovskite layer by different methods: doctor-blading, ink-jet printing, hot-press transfer, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a high PCE, a PVSC must possess high operational stability if it is to find wide applicability [26,30]. Incorporating an inorganic material [27,28] or hydrophobic polymer under the cathode layer can be an effective method to protect the PVSC from the permeation of oxygen and humidity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating an inorganic material [27,28] or hydrophobic polymer under the cathode layer can be an effective method to protect the PVSC from the permeation of oxygen and humidity [29]. For example, hydrophobic poly(methyl methacrylate) (PMMA) has been incorporated into PVSCs to enhance their operational and storage stabilities [30][31][32][33]. Kundu (FF) of the PVSC, while also inhibiting the permeation of moisture into the MAPbI3 layer and increasing the storage stability [32].…”
Section: Introductionmentioning
confidence: 99%